Analisa Perawatan Dan Perbaikan Motor Starter Tipe Konvensional Pada Engine Toyota Kijang Innova 2.4 G A/T - Merpatih Merpatih; Abdul Halim; Imam Imam; Samiran Samiran (MEDIA PERSPEKTIF : Journal of Technology, 2022)
The starter motor is a component in a vehicle that functions to start the engine for the first time by converting electric energy into rotary power. Where the motor starter system is used to rotate the crankshaft and then move the pistons so that the engine can start. Generally, cars use an electric motor combined with a magnetic switch to move the pinion gear that rotates to the ring gear and surrounds the flywheel and is bolted to the crankshaft. The starter motor must be able to produce a large moment from the small power available in a battery that has direct current. The purpose of this research is to find out how the mechanism of the starter motor works on the Toyota Kijang Innova 2.4 GA/T.  The research method used is a qualitative method, namely the method used to examine the components of the starter motor on the Toyota Kijangv Innova 2.4 GA/T. The results of this study indicate that the components on the starter motor of the Toyota Kijang Innova 2.4 GA/T  are all in standard condition.